“When a foreign language learner becomes a foreign language teacher…” – A cross-cultural study into the affective domain of teaching - Kiliańska-Przybyło, Grażyna; Bedir, Hasan; Can, Cem (Glottodidactica, 2012)
The aim of this paper is to characterize early experiences of future teachers of English in Polish and Turkish contexts; describe their emotions and attitudes as well as analyze their evaluations of the past situations. When a foreign language learner becomes a foreign language teacher…, firstly s/he has to transform from a FL student to a FL teacher, develop the ability to talk about one’s early experiences and relate them to future growth. In this sense, narrative inquiry largely helps in contextualizing and transforming one’s experience. The data collected for the study involve narratives produced by Turkish and Polish teacher trainees.